PENGARUH UKURAN PERUSAHAAN, LEVERAGE, AUDITOR SWITCHING, DAN SISTEM PENGENDALIAN INTERNAL PADA AUDIT DELAY - Wiryakriyana, A A Gede; Sari Widhiyani, Ni Luh (E-Jurnal Akuntansi; Vol 19 No 1 (2017), 2017)
This study aimed to analyze the factors that affect audit delay on manufacturing companies listed in Indonesia Stock Exchange year period 2013-2015. Factors tested in this study is the size of the company, leverage, switching auditors, and internal control systems as independent variables. The sampling technique used in this research is purposive sampling with total sample of 76 companies. Analysis of data using multiple linear regression. The results showed that company size has no effect on audit delay, leverage positive effect on audit delay, auditor switching negative effect on audit delay, and internal control system and has no effect on audit delay .
Keywords: audit delay, firm size, leverage, switching auditors, the internal control system.